A novel compliant piezoelectric actuated symmetric microgripper for the parasitic motion compensation. (January 2021) - Kumar Das, Tilok; Shirinzadeh, Bijan; Al-Jodah, Ammar; Ghafarian, Mohammadali; Pinskier, Joshua
Highlights: A novel compliant microgripper is proposed for precise positioning tasks. A parasitic motion minimization approach is adopted by the structural design. The key characteristics of the microgripper are investigated experimentally. The parasitic motion of the microgripper is obtained as 0.59% of the desired motion. A high precision output motion of  ± 5 nanometer is achieved. Abstract: With the advancement of technology, the demand for high precision micrograsping/releasing task is increasing. This paper presents a compliant piezoelectric actuated microgripper for precise positioning tasks. A parasitic motion minimization approach is adopted by the structural design of the microgripper. The over-constrained leaf flexure-based parallelogram mechanisms are accommodated with the displacement transmission and amplification mechanisms for achieving a linear output motion of the microgripper's jaws. The microgripper utilizes a two-stage displacement transmission and amplification mechanism. Two lever-type mechanisms are symmetrically connected with the bridge-type mechanism to amplify the output displacement of the piezoelectric actuator. The microgripper design is optimized through the computational method to achieve high performance in terms of the low parasitic motion and large output displacement. The effect of the design parameters on the characteristics of the microgripper is investigated using the computational analysis and the experimental studies are conducted to verify the characteristics of the microgripper. The experimental results show that the microgripper has a low parasitic motion. Further, the microgripper achieves a high precision motion resolution.